Review on frequency reconfigurable antenna using substrate-integrated waveguide for cognitive radio application - AL-Fadhali, Najib; A. Majid, Huda; Omar, Rosli; Abdul Sukora, Jumadi; A. Rahim, Mohamad K.; Zainal Abidin, Zuhairiah; Al-Bukhaiti, Mohammed; Momin, Abdul Malik; Abo Mosali, Najmaddin (Taylor & Francis, 2021)
Cognitive radio (CR) exploits the spectrum efficiently and minimizes the interference between different devices. Meanwhile, multiband frequency-reconfigurable antennas (FRA) are desirable for CR where it is beneficial to dynamically reconfigure a single antenna to be transmitted and/or received on multiple frequency bands. As stated by the literature review, there is a dearth of work into multiband FRA that is directly applied in CR applications with substrate-integrated waveguide (SIW) technology. Frequency-reconfigurable SIW (FRSIW) is seen as promising for the development of microwave and millimeter waveband antennas. This study’s key objective is for the technical operational advances of SIW antennas to be summarized and compared. The design structure of FRSIW elements using different techniques is discussed in detail. The findings supported the effectiveness of FRSIW for managing radio spectrum to work in most efficient way.